Law Enforcement of Criminal Fraud in Online Buying and Selling in Surakarta - Ibrahim Nurrohman; Muchamad Iksan (Universitas Muhammadiyah Surakarta, 2023)
The purpose of this study is to investigate the law enforcement agencies against online trading fraud in Surakarta Police Station, to know the obstacles in cracking down on online trading fraud in Surakarta Police Station, and to know from the perspective of online trading. Makassid Shariah. The approach method used in this paper is the legally demonstrative approach. This type of research in this article is descriptive research. Data sources have primary and secondary data. The findings obtained indicate that the legal protection of victims in Indonesia's statutory law includes several laws, including the Constitution of 1945, Law No. 13 of 2006 on Protection of Witnesses and Victims, and Law No. 39 of 1999 on Human Rights and Human Rights. Indicates that it is stipulated by a certain law. Law No. 11 of 2008 on Information and Electronic Transactions. As a strategic step to overcome these technical hurdles, it is critical that authorities build expertise in cybercrime and network security. Islamic law, as verse 105 of the Koran Surah an‐Nar and the Hadith of the Prophet, clearly states regarding fraud in sales transactions: Those who do treason and manipulation., the place of hell. (narrated by Ibn Hiban).